2019
DOI: 10.4049/jimmunol.1801004
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Signaling and Its Effects on Lymphopoiesis of CAR-Armed Hematopoietic Stem and Progenitor Cells

Abstract: Long-term survival of adoptively transferred chimeric Ag receptor (CAR) T cells is often limited. Transplantation of hematopoietic stem cells (HSCs) transduced to express CARs could help to overcome this problem as CAR-armed HSCs can continuously deliver CAR+ multicell lineages (e.g., T cells, NK cells). In dependence on the CAR construct, a variable extent of tonic signaling in CAR T cells was reported; thus, effects of CAR-mediated tonic signaling on the hematopoiesis of CAR-armed HSCs is unclear. To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Analysis of gene expression was performed using quantitative PCR analysis as described, with slight modifications. 41,42 Briefly, triplets of 1*10 4 PC3 cells were seeded and cultivated with RevCAR T cells in the presence or absence of RevTMs. After incubation for 24 h, co-transduced RevCAR T cells were sorted for EGFP + /mCherry + expression under exclusion of PI + cells.…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of gene expression was performed using quantitative PCR analysis as described, with slight modifications. 41,42 Briefly, triplets of 1*10 4 PC3 cells were seeded and cultivated with RevCAR T cells in the presence or absence of RevTMs. After incubation for 24 h, co-transduced RevCAR T cells were sorted for EGFP + /mCherry + expression under exclusion of PI + cells.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Sorting and analysis of gene expression profile were performed as described earlier. 41 The n-fold change of gene expression between incubation with COS RevTM + SIG RevTM versus w/o RevTM was calculated using the ΔΔC P method.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…During their ex vivo expansion, CAR tonically signals to induce the exhaustion phenotype 12 . Antigen-independent tonic signalling is reported to affect the lymphopoiesis of CAR-engineered haematopoietic stem cells (HSCs) and promote NK cell-like development 13 , 14 . In contrast, T cells derived from CD19 CAR-engineered iPSCs show phenotypic similarities to γδ T cells 5 .…”
Section: Resultsmentioning
confidence: 99%
“…1c ). Recent investigations reported that 1928z transduction into HSCs impaired T-cell differentiation capability 13 , 14 and promoted NK-like cell development by suppressing the transcription factor BCL11B, which is indispensable for T-lineage development of lymphoid progenitors during early phases of ex vivo T-cell generation. It could be a possible reason also for T-cell differentiation from 1928z CAR-transduced iPSC 5 .…”
Section: Resultsmentioning
confidence: 99%
“…T-iPSCs with RAG2 knockout and non-T-iPSCs with transduced TCR can also help avoid unpredictable TCR generation [ 89 ]. It is notable that CAR, as an artificial fusion molecule, may disturb the normal pattern of T lymphopoiesis [ 123 ] and this can be overcome by constructing conditional expression cassettes at the stem cell level. Additionally, eliminating the expression of GM-CSF in CAR-T cells mitigates neurotoxicity and cytokine release syndrome (CRS) [ 124 126 ].…”
Section: T-cell Generation Meets Gene Editingmentioning
confidence: 99%